Self-Inflicted Injuries Among Young Age Group in Lahore, Pakistan - Saima Manzoor, Urooj Husain, Imran Jawaad, Durdana Zafar, Zubia Iqbal, Nazia Yasmin (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Self-inflicted injuries have always attracted medicolegal experts. These injuries are produced by a person on his own body for ulterior motives. Majority of such cases are observed among adults dominated by male gender. Such cases when observed among young age group are alarming and need to be explored. Excessive use of social media, unresolved social issues, large family size, lack of education, family conflict are among the leading causes of rise in such cases. Parental guidance in all such cases need to stressed as such children who has some psychiatric problems are already highlighted and known to the parents, close supervision of such adolescents could help them to prevent such grave incidences. The emotional bond between children and parents at this age is quite strong any emotional disturbance if properly handled at this stage could lead to a healthy state of mind rather than to be a stigma resulting in self-inflicted injuries which shall leave a long lasting effect on the emotional status of the child. Material and Method: Data from three major hospitals from Lahore catering paediatric cases was collected from January 2000 to December 2010. This data was analyzed for further study. Inclusion criteria: Those cases which were declared self-inflicted case by the examining medical officer were included in the study. Results: Results showed that males were more involved in self-infliction and the dominant weapon used sharp edged weapon followed by blunt weapon. Most common site of such injuries is wrist. Females were involved to a lesser extent in such cases, however, the weapon most commonly used among females was also sharp edged and wrist was the most common site of such injuries. Conclusion: Large family size, loose association between parents and children, low socioeconomic condition, family headed by single parent usually shows higher incidence of such injuries among young age group. Keywords: Self-inflicted injuries, Medico-legal issues, Age group.